Pengaruh Susunan Laminasi Serat Gelas Terhadap Kekuatan Tarik Komposit Untuk Bodi Lori Inspeksi - Henry Widya Prasetya; Dadang Sanjaya Atmaja; Ilham Satrio Utomo (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2020)
Composite material is a type of new, engineered material consisting of two or more materials where the properties of each material differ from one another both in chemical and physical properties and remain separate in the final material. Composite materials have many advantages, one of which is lighter weight and corrosion resistance. In this study, composites made from glass fiber were carried out with variations in the arrangement of laminates, in order to select the material which was then applied to the manufacture of the inspection lorry body. Composites were made using the hand lay-up method. Tensile test specimens made according to ASTM D-638. The results of the tensile test show that the highest tensile strength of glass fiber composite material for the inspection lorry body is 5.45 MPa and the lowest tensile strength is 4.62 MPa. Keyword: composite, glass fiber, tensile test, inspection lorry